High-Stability Silver Nanowire–Al2O3 Composite Flexible Transparent Electrodes Prepared by Electrodeposition - Honglong Ning (MDPI AG, 2021)
Silver nanowire (AgNW) conductive film fabricated by solution processing was investigated as an alternative to indium tin oxide (ITO) in flexible transparent electrodes. In this paper, we studied a facile and effective method by electrodepositing Al2O3 on the surface of AgNWs. As a result, flexible transparent electrodes with improved stability could be obtained by electrodepositing Al2O3. It was found that, as the annealing temperature rises, the Al2O3 coating layer can be transformed from Al2O3·H2O into a denser amorphous state at 150 °C. By studying the increase of electrodeposition temperature, it was observed that the transmittance of the AgNW–Al2O3 composite films first rose to the maximum at 70 °C and then decreased. With the increase of the electrodeposition time, the figure of merit (FoM) of the composite films increased and reached the maximum when the time was 40 s. Through optimizing the experimental parameters, a high-stability AgNW flexible transparent electrode using polyimide (PI) as a substrate was prepared without sacrificing optical and electrical performance by electrodepositing at −1.1 V and 70 °C for 40 s with 0.1 mol/L Al(NO3)3 as the electrolyte, which can withstand a high temperature of 250 °C or 250,000 bending cycles with a bending radius of 4 mm.